Investigating the Effect of Magnesium in Preventing Tremors after Anesthesia: A Systematic Review - Esmailpour Roshan, Mojtaba; Jafari, Hanieh (Asian Pacific Journal of Cancer Biology, 2024)
Background and Purpose: In addition, magnesium is prescribed intravenously, epidurally, or intraperitoneally, each of which may have different effects depending on the surgical procedure. In this review, we searched for randomized clinical trials that compared preoperative magnesium administration with controls and included studies that assessed chills as a primary and possible outcome. change. The main objective of this study was to evaluate the effect of preoperative magnesium in the prevention of postoperative chills. Materials and methods: This article is a systematic review that searched for all quality articles published in the Cochrane database until the end of 2020. References were checked, PubMed and Web of Science 55,555. Results: The initial search identified 3,294 publications. 64 articles were included in this study. The results showed that the frequency of colds in the group receiving intravenous, epidural and intraperitoneal magnesium was significantly reduced compared to the control group. Conclusion: Prophylactic use of magnesium can reduce the severity and number of post-anesthetic chills and other post-anesthetic symptoms.